AIEC Pathobiont Instigates Chronic colitis in Susceptible Hosts by Altering Microbiota composition - Chassaing, Benoit (2013)
BACKGROUND: IBD is driven by a seemingly aberrant immune response to the gut microbiota with disease development dictated by genetics and environmental factors. A model exemplifying this notion is our recent demonstration that colonization of adherent-invasive E. coli (AIEC) during microbiota acquisition drove chronic colitis in mice lacking the flagellin receptor TLR5 (T5KO). T5KO colitis persisted beyond AIEC clearance and requires TLR4 and the NLRC4 inflammasome. We hypothesized that AIEC instigates chronic inflammation by increasing microbiota levels of LPS and flagellin. GOAL: Examine if transient AIEC colonization lastingly alters levels of LPS and flagellin and changes microbiota composition. METHODS: Germ-free mice (WT and T5KO) were inoculated with AIEC strain LF82 and placed in standard housing allowing a complex microbiota that eliminated AIEC in both mice strains. Feces were assayed for the inflammatory marker lipocalin-2, bacterial loads, and microbiota composition by pyrosequencing. Fecal LPS and flagellin bioactivity were measured via a cell-based reporter assay. RESULTS: Transient AIEC colonization, in WT mice, did not alter inflammatory markers, bacterial loads, microbiota composition, nor its pro-inflammatory potential. In contrast, transient AIEC colonization of T5KO mice drove chronic inflammation, which correlated with microbiota components having higher levels of bioactive LPS and flagellin. Such AIEC-induced elevation of LPS and flagellin persisted well beyond AIEC clearance, required AIEC be flagellated, and was associated with alteration in microbiota species composition including a loss of species diversity. CONCLUSION: AIEC, and perhaps other pathobionts, may instigate chronic inflammation in susceptible hosts by altering the gut microbiota composition so as to give it an inherently greater ability to activate innate immunity/pro-inflammatory gene expression.